The Restorative Justice Implementation at the Investigation Stage: Riview on Justice Perspective - Aprianto, Rezmi Angga; Wahyuningsih, Sri Endah (LAW FACULTY UNISSULA, 2024)
The research objectives in this study are to describe and analyze the application of restorative justice at the investigation stage of criminal cases at the Kendal Resort Police, to analyze legal thinking by Kendal Police Investigators regarding accountability in the implementation of restorative justice at the Investigation stage. This research uses a sociological juridical approach, with quantitative descriptive research methods. The data used is primary and secondary data which will be analyzed qualitatively. Research problems are analyzed using the theory of legal objectives, the theory of legal certainty. The results of the research concluded that the implementation of Restorative Justice at the Investigation stage of criminal cases at the Kendal Police Department means that criminal cases can be closed by law and the prosecution is terminated based on Restorative Justice if the following conditions are met: the suspect is committing a crime for the first time, the crime is only threatened with a fine or threatened with imprisonment for not more than 5 (five) years; and the criminal act is committed with the value of the evidence or the value of losses incurred as a result of the criminal act not exceeding IDR 2,500,000.00 (two million five hundred thousand rupiah).”Keywords:Crime; Justice; Police; Restorative; Review.